Equilibrium Moisture Sorption Isotherms of Aspirin (Journal of Engineering, 2013)
Equilibrium Moisture sorption isotherms are very important in drying and storage analysis. Experimental moisture equilibrium data (adsorption and desorption) of Aspirin were determined using the static method of saturated salt solutions and that by exposing the material to different conditions of temperatures and water activities. Three different temperatures (25, 30, 40Cº) and water activities in the range of (6.3- 83.6%) were used. The results showed that the equilibrium moisture content increased with the increase in water activity at any temperature and decreased with temperature increase at constant water activity. The water activity increases with increasing in temperature when moisture content was kept constant. The sorption isotherm curves are of type II according to Brunauer`s classification. The hysteresis effect was not distinctly expressed only for equilibrium sorption values of Aspirin at 25ºC. The experimental results were fitted to two sorption models (GAB and Henderson).The average relative deviation between the experimental and calculated data were obtained to select the best model. The GAB and Henderson models, obtaining values of 3.54 and 1.42 % average relative deviation and coefficient of regression of 0.98 and 0.977 respectively. The Henderson model was found to be the best fit out of the two models to predict the sorption behavior of Aspirin.